Nutritional Assessment Using Modified SGA Score and Its Correlation with Biochemical Profile Among Maintenance Hemodialysis Patients: A Cross Sectional Study at Multiple Hemodialysis Centers in Dhaka - Rahman, Mohammad Syfur; Akhter, Mahbuba; Ershad, Sk Md; Sultana, Tayeba; Sultana, Tahera; Mondal, Swapan Kumar (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Patients on maintenance hemodialysis are vulnerable to multitude of health-related issues, malnutrition being one of them. It is a key predictive factor for morbidity and mortality among patients on maintenance hemodialysis. The primary objective of the study was to assess the severity of malnutrition in patients undergoing maintenance hemodialysis, using modified subjective global assessment score and correlate it with biochemical parameters like blood hemoglobin, serum creatinine, serum albumin, serum pre-albumin, serum triglyceride and serum total cholesterol. Cross-sectional study from July 2016 to June 2017 was conducted at hemodialysis unit of SSMC & MH, BSMMU, BIRDEM hospital and NIKDU, Dhaka, among 80 maintenance hemodialysis patients. Adult patients over the age of 18 years and on regular (>_ 2 sessions per week) hemodialysis for more than 3 months without any acute infection were enrolled. Nutritional status of the patients was evaluated using modified subjective global assessment score and compared with biochemical parameters for any correlation between them. Based on the modified SGA scores, of the 80 patients, 10% were well nourished and the rest were mildly malnourished, showing a high degree of malnutrition among respondents. There was strong positive correlation between modified subjective global assessment score and age. Modified SGA score also showed statistically significant negative correlation with serum creatinine, serum albumin and serum pre-albumin. Data obtained from this study confirm that modified subjective global assessment score can be used as a reliable index for identifying patients at risk for malnutrition and it correlates well with some of the biochemical profile. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):14-19